Paenibacillus plantiphilus sp. nov. from the plant environment of Zea mays - Kämpfer, Peter; Lipski, André; Lamothe, Lucie; Clermont, Dominique; Criscuolo, Alexis; McInroy, John A.; Glaeser, Stefanie P.; Justus Liebig University Giessen (My University, 2023)
A Gram-strain positive, aerobic, endospore-forming bacterial strain (JJ-246T) was isolated from the rhizosphere of Zea mays. The 16S rRNA gene sequence similarity comparisons showed a most closely relationship to Paenibacillus oenotherae DT7-4T (98.4%) and Paenibacillus xanthinolyticus 11N27T (98.0%). The pairwise average nucleotide identity and digital DNA-DNA hybridisation values of the JJ-246T genome assembly against publicly available Paenibacillus type strain genomes were below 82% and 33%, respectively. The draft genome of JJ-246T shared many putative plant-beneficial functions contributing (PBFC) genes, related to plant root colonisation, oxidative stress protection, degradation of aromatic compounds, plant growth-promoting traits, disease resistance, drug and heavy metal resistance, and nutrient acquisition. The quinone system of strain JJ-246T, the polar lipid profile and the major fatty acids were congruent with those reported for members of the genus Paenibacillus. JJ-246T was shown to represent a novel species of the genus Paenibacillus, for which the name Paenibacillus plantiphilus sp. nov. is proposed, with JJ-246T (= LMG 32093T = CCM 9089T = CIP 111893T) as the type strain.
Keywords: ddc:630